Endoscopic Evaluation of Swallowing in Patient with Tetanus Followed by Myasthenia Gravis as its Complication - Muyassaroh Muyassaroh; Rachma Purnama Sari; Rery Budiarti (Universitas Muhammadiyah Yogyakarta, 2022)
Flexible Endoscopic Evaluation of Swallowing (FEES) provides direct visualization of the pharynx and larynx immediately before and after a swallow in a patient with dysphagia. Dysphagia is the difficulty in swallowing solid or liquid food. It is a symptom of an underlying disease like tetanus and myasthenia gravis. This case report showed the important role of FEES in patients with dysphagia due to tetanus followed by myasthenia gravis as its complication. A 58-year-old man had complaints of severe difficulty in swallowing followed by complaints of fever and whole body seizures, which supported the diagnosis of tetanus. In the course of the disease, symptoms and the results of supporting examinations indicated the presence of myasthenia gravis. Comprehensive management had done with colleagues in internal medicine, neurology and medical rehabilitation. That condition improved and the complaints disappeared after one month. It can be concluded that FEES played an important role in diagnosing dysphagia. It could identify the modification of food consistencies and therapeutic maneuvers to prevent an aspiration for a patient with dysphagia as the early symptom of tetanus which caused neurotransmitter damage that broke muscle nerve junctions. It is also one of the predisposing factors for autoimmune conditions in myasthenia gravis. Correct diagnosis and comprehensive management give a better improvement for the disease.